Effect of Iodine Solution on Histopathology of Rats Kidney Induced by Lead Acetate - Zawata Afnan; Biomechy Oktomalio Putri; Miftah Irramah (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Lead is a metal that is toxic to the environment and the human body. Lead can cause oxidative stress in body tissues and organs, including the kidneys. Iodine can function as an antioxidant because it can inhibit the increase in free radicals so that oxidative stress does not occur. This study aims to see the effect of giving iodine solution on the histopathological picture of lead acetate-induced rat kidney. This study was an experimental study using 18 Rattus novergicus rats which were divided into 3 groups, namely the negative control group which was only given standard feed, positive control which was given standard feed and lead acetate 10 mg/Kg BB, and the treatment group which was given standard feed. , 10 mg/Kg BB lead acetate, and 12.5 mg iodine solution for 19 day. The rat kidney damage scores were 4 for the positive group, 2 for the treatment group, and 1 for the negative group. The conclusion of this study is that there is an effect of giving iodine solution in preventing damage to the kidney cells of rats induced by lead acetate.